Stilistika dan Al-Qur’an: Fenomena Budaya Uslûbiyah Bangsa Arab - Muhammad Sapil (Program Studi Ilmu Al-Quran dan Tafsir STIU Darul Quran, 2022)
This paper discusses the correlation of modern linguistics with the linguistics contained in the Al-Qur'an, then explains the phenomenon of Arabic language style which has become a culture, either before or after the Al-Qur'an was revealed, and finally describes how the influence of language literature Al-Quran on the uslûbiyah culture of the Arab nation. The explanation in this paper is in the form of descriptive which relies on explanations from the literature in accordance with the theme so that the method of analysis that is appropriate to this theme is descriptive-analytic, this method also includes qualitative research based on library research (library research). The results of the discussion of this article conclude that stylistics is a Western language discipline that has an equivalent to uslûbiyah science. Uslûbiyah is a separate scientific discipline which is formed from the science of Balaghah and has a central function with other linguistics. The Qur'an, which is a source of uslûbiyah (stylistic) studies, greatly influenced the rhetorical style of the Arab nation after it was revealed to the Prophet Muhammad, especially in terms of style, content, and purpose.